Dynamic research support for academic libraries - Hoffman, Starr (Facet Publishing, 2016)
This inspiring book will enable academic librarians to develop excellent research and instructional services and create a library culture that encompasses exploration, learning and collaboration. Higher education and academic libraries are in a period of rapid evolution. Technology, pedagogical shifts, and programmatic changes in education mean that libraries must continually evaluate and adjust their services to meet new needs. Research and learning across institutions is becoming more team-based, crossing disciplines and dependent on increasingly sophisticated and varied data. To provide valuable services in this shifting, diverse environment, libraries must think about new ways to support research on their campuses, including collaborating across library and departmental boundaries. This book is intended to enrich and expand your vision of research support in academic libraries by; inspiring you to think creatively about new services; sparking ideas of potential collaborations within and outside the library, increasing awareness of functional areas that are potential key partners; providing specific examples of new services, as well as the decision-making and implementation process; and encouraging you to take a broad view of research support rather than thinking of research and instruction services, metadata creation and data services as separate initiatives.